Infrared–metabolomics approach in detecting changes in andrographis paniculata metabolites due to different harvesting ages and times - Yusof, Nur A'thifah; Isha, Azizul; Ismail, Intan Safinar; Khatib, Alfi; Shaari, Khozirah; Abas, Faridah; Rukayadi, Yaya (John Wiley & Sons, 2015)
BACKGROUND: The metabolite changes in three germplasm accessions of Malaysia Andrographis paniculata (Burm. F.) Nees, viz. 11265 (H), 11341 (P) and 11248 (T), due to their different harvesting ages and times were successfully evaluated by attenuated total reflectance (ATR)–Fourier transform infrared (FTIR) spectroscopy and translated through multivariate data analysis of principal component analysis (PCA) and orthogonal partial least square–discriminant analysis (OPLS-DA). This present study revealed the feasibility of ATR-FTIR in detecting the trend changes of the major metabolites – andrographolide and neoandrographolide – functional groups in A. paniculata leaves of different accessions. The harvesting parameter was set at three different ages of 120, 150 and 180 days after transplanting (DAT) and at two different time sessions of morning (7:30–10:30 am) and evening (2:30–5.30 pm).